2017
DOI: 10.3748/wjg.v23.i25.4529
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine prevents oxidative stress in a model of portal hypertension

Abstract: AIMTo evaluate the protective effects of glutamine in a model of portal hypertension (PH) induced by partial portal vein ligation (PPVL).METHODSMale Wistar rats were housed in a controlled environment and were allowed access to food and water ad libitum. Twenty-four male Wistar rats were divided into four experimental groups: (1) control group (SO) - rats underwent exploratory laparotomy; (2) control + glutamine group (SO + G) - rats were subjected to laparotomy and were treated intraperitoneally with glutamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
5
0
3
Order By: Relevance
“…Several studies in humans have shown that Gln modulates the expression of genes related to the activation of pathways involved in several disease states[22-25]. Furthermore, studies conducted in different experimental models have demonstrated beneficial effects of Gln on the rat liver, bowel, and stomach[21,26-30].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in humans have shown that Gln modulates the expression of genes related to the activation of pathways involved in several disease states[22-25]. Furthermore, studies conducted in different experimental models have demonstrated beneficial effects of Gln on the rat liver, bowel, and stomach[21,26-30].…”
Section: Introductionmentioning
confidence: 99%
“…The very early age at PVT presentation of our MTHFR TT carriers is unusual and several factors may contribute to this prematurity: leaking of bacterial lipopolysaccharide from the intestine into the portal vein may cause in ammasome activation [15,16] and thrombin generation [17,18], the latter further supported by the oxidation of lipids, abundant in the portal circulation [19,20]; on this background, the additional oxidative effect of elevated HC may anticipate acute thrombosis in MTHFR TT carriers [8].…”
Section: Discussionmentioning
confidence: 99%
“…The partial portal vein ligation model is the most commonly used to study prehepatic PH. Several experimental studies have shown that partial portal vein ligation produces abnormalities equivalent to PH in humans 17 .…”
Section: Discussionmentioning
confidence: 99%